PENGARUH TATA KELOLA PEMERINTAHAN, ASIMETRI INFORMASI, EFEKTIVITAS PENGENDALIAN INTERNAL, DAN KEADILAN DISTRIBUTIF TERHADAP KECURANGAN (fraud) (Studi Empiris Pada OPD Kota Dumai) - Taufeni Taufik; Volta Diyanto Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study examines the impact of good governance, information asymmetry, the effectiveness of internal control and distributive justice against fraud. The population in this research is Dumai City Device Organization of 34 OPD. Of the existing population then obtained samples in this study as many as 102 respondents. Sampling technique using purposive sampling method, The technical analysis used in this study is multiple linear regression. While data processing method used by SPSS 21.0 as software to process data. The results showed that good governance effect on fraud (fraud) with a significant value of 0.000. information asymmetry has a significant effect of 0.009 on fraud. the effectiveness of internal control has a significant effect of 0.000 against fraud. And distributive justice has a significant effect of 0.000 on the fraud.Keywords : Good Governance, Inform